Verbal Abuse by Netizens on Social Media Against A Youtuber’s Childfree Decision Statement Named Gita Savitri - Ariibah, Aulia Azka; Zakiyyah, Hamidah (RSF Conference Series: Business, Management and Social Sciences, 2023)
Verbal abuse is violence that hurts the other person verbally by saying harsh utterances that can impact the victim’s psychologist. Social media is widely used to ease users communicating with others freely; this kind of platform found many utterances contain verbal abuse. This study aims to categorize and explain the types of verbal abuse directed against influencers as well as a YouTuber named Gita Savitri, who is committed to being childfree. The subjects in this study were words that contained elements of verbal abuse in the form of responses to comments or posts on social media, Twitter and Instagram towards Gita Savitri. The data were obtained using the observation method by observing verbal abuse utterances directed to Gita Savitri’s childfree statement gathered from Twitter and Instagram. In this study, a qualitative research methodology was adopted, and the research phase included discourse observation, data collection, data filtering, and data analysis. The researchers found that verbal abuse utterances in this study contain various four types, namely direct verbal abuse, indirect verbal abuse, repressive verbal abuse, and alienative verbal abuse. The data obtained in this research showed as many as 82 data verbal abuse found on Twitter posts and Gita Savitri’s Instagram comment section. From 82 data obtained, the researchers classified into 49 direct verbal abuse data, 24 indirect verbal abuse data, five repressive verbal abuse data, and four alienative verbal abuse data.